THE INFLUENCE OF SOCIAL MOVEMENTS ON PUBLIC POLICY: A CASE STUDY OF THE RUMAH BAKAU JAYAPURA - Kadun MT, Alienra Davry Nanda (JPASDEV : Journal of Public Administration and Sociology of Development, 2024)
Rumah Bakau Jayapura is a community working in the environmental sector. This community represents a new social movement that practices the principles of environmentalism. The strategic goal of social movements is to influence public policy. The aim of this research is to examine the influence of the Rumah Bakau social movement on government policies. This descriptive research uses documentation and observation techniques. The researcher uses the Galego analysis model to describe the relationship and influence of social movements on politics. Results provide information about the goals, strategies and effects of social movements. Rumah Bakau has a utopian goal: to save the environment. The goal of this community is simply to seek recognition of the environment as a new entity that also needs to be included in decision making. Rumah Bakau strategy consists of direct and indirect actions. However, this community failed to influence public policy. This research concludes the importance of choosing a social movement strategy for it can be successful.